2019
DOI: 10.3389/fmed.2019.00102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Synovial Biopsy

Abstract: The synovial tissue is a primary target of multiple diseases characterized by different pathogenic mechanisms, including infective, deposition, neoplastic, and chronic immune-inflammatory pathologies. Synovial biopsy can have a relevant role in differential diagnosis of specific conditions in clinical practice, although its exploitation remains relatively limited. In particular, no validated synovial-tissue-derived biomarkers are currently available in the clinic to aid in the diagnosis and management in most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…The synovial biopsy is considered the final and last choice for establishing the diagnosis of chronic monoarthritis. It is assumed that in cases of undifferentiated arthritis, a synovial biopsy can facilitate the diagnostic process [ 6 , 14 ]. Results of our study showed that synovial biopsy could establish a definite diagnosis in one-third of cases with undifferentiated chronic knee monoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The synovial biopsy is considered the final and last choice for establishing the diagnosis of chronic monoarthritis. It is assumed that in cases of undifferentiated arthritis, a synovial biopsy can facilitate the diagnostic process [ 6 , 14 ]. Results of our study showed that synovial biopsy could establish a definite diagnosis in one-third of cases with undifferentiated chronic knee monoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the mentioned categories, undifferentiated arthritis refers to the condition that arthritis could not be categorized as rheumatoid arthritis or other classes of definite arthritis. Undifferentiated arthritis might indicate the early phase of an established disease or remain an entity that does not fit into any category of rheumatologic diagnoses [ 6 , 7 ]. Establishing a definite diagnosis for undifferentiated arthritis disorders is a long-standing challenge in rheumatology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irrespective of the clinical diagnosis, the synovial membrane in the course of chronic inflammatory arthritis is characterized by a number of common histopathological changes, including neoangiogenesis, proliferation and activation of the tissue stroma, and infiltration of the sublining layer by cells of the innate and adaptive immune system [124][125][126][127]. Notwithstanding these general similarities, synovial inflammatory features greatly vary in terms of cellular composition and reciprocal spatial arrangements across different disease entities and within a same disease, possibly reflecting divergent pathogenetic pathways [128,129].…”
Section: Synovial Pathologymentioning
confidence: 99%